Solvent-resistant polyimide film as well as preparation method and application thereof
By introducing carboxyl-containing diamine monomers into the polyimide film and performing metal ion coordination crosslinking, solvent-resistant microporous polyimide films were prepared, which solved the problem of difficult to take into account the separation efficiency and permeability of existing film materials, and achieved efficient and stable crude oil separation.
Patent Information
- Application Number
- CN202411757399.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-12-03
AI Technical Summary
The existing membrane materials used for crude oil separation are difficult to take into account the separation efficiency and permeability, and the long-term stability is poor, making it difficult to achieve industrial production.
Polyimide segments are prepared by introducing carboxyl-containing diamine monomers, and a solvent-resistant microporous polyimide film is formed by metal ion coordination crosslinking, thereby improving the solvent resistance and physical and chemical stability of the film.
It realizes high throughput and efficient separation of organic molecules of different molecular weights, has excellent solvent resistance and physical and chemical stability, and is suitable for separation of light crude oil.
Smart Images

Figure CN119565411A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of membrane separation, and in particular to a solvent-resistant polyimide film and a preparation method and application thereof. Background Art
[0002] The separation of liquid mixed hydrocarbons is a challenging project. In industrial applications, a large amount of energy is consumed to process and successfully separate complex mixtures. The separation and purification of crude oil accounts for about 3% of global industrial energy consumption. Although thermal distillation technology can complete the distillation process of light crude oil according to different boiling points, this high-energy consumption process is not in line with the concept of sustainable development. Membrane separation technology has the advantages of low energy consumption and high efficiency, and is expected to promote the sustainable development of crude oil fractionation. However, "compact" organic solvent nanofiltration membranes for light crude oil separation are relatively scarce. The main reason is that most polymer membranes are extremely easy to swell during the separation process, resulting in extremely low separation efficiency. Widely used polyimide materials such as It is easy to swell in hydrocarbon solvents, resulting in low separation efficiency. Due to their high thermal, mechanical, and chemical stability, they are currently widely used in gas separation. However, their extremely high solvent stability results in a very low membrane swelling rate, resulting in poor permeability, which is not conducive to large-scale industrial development. Consequently, as commercial membranes cannot achieve good separation efficiency, a number of new membrane materials have been developed in recent years for light crude oil separation.
[0003] The structure of a light crude oil separation membrane should possess the following characteristics: (1) an ultra-thin separation layer of a microporous polymer membrane ensures high solvent flux; (2) a hydrophobic polymer facilitates the wetting and penetration of light crude oil into the membrane; and (3) the membrane's resistance to swelling maintains stable separation performance. Considering these design principles, the daunting challenge of separating light crude oil using membrane technology has placed higher demands on the design of new materials for light crude oil separation.
[0004] In order to solve the above problems, the prior art uses a variety of methods to prepare different membranes to improve the membrane's swelling resistance, physicochemical stability and crude oil separation efficiency. For example, US20190276454A1 discloses a series of spirocyclic microporous polymers connected with N-aryl bonds. The flexible molecular chains are connected and the strong hydrogen bonds between molecules make the molecular chains have microporosity that is not connected to each other, so that the molecular chains have good swelling resistance in organic solvents. The dependence of SBAD performance on pore structure and dynamic movement allows the fractionation of complex mixtures to be expanded and can be converted into real crude oil fractions. WO2022123497A1 discloses a PTA-OH asymmetric film with an ultra-thin selective layer prepared by a thermal cross-linking method. The selective layer controlled at a thickness of 10nm has sub-nano channels, which can be used to separate hydrocarbons and can address the solvent resistance and aging problems of the membrane. US20230140883A1 discloses a new membrane suitable for separation applications, as well as a method for manufacturing the membrane and the use of the membrane in a series of separation applications. Hydrophobic polyamide nanomembranes, prepared by interfacial polymerization of self-assembled vesicles, transport hydrophobic liquids at rates over 100 times faster than conventional hydrophilic nanomembranes. In the fractionation of light crude oil, the membrane thickness was controlled to ~10 nanometers, achieving a permeability an order of magnitude higher than that of currently state-of-the-art hydrophobic membranes while maintaining similar size and class separations. This high permeability expands the potential for using ultrathin nanomembranes in crude oil fractionation. However, the preparation methods for these ultrathin nanomembranes are complex, with poor reproducibility, and the overly thin separation membrane layers suffer from poor long-term stability during use, making industrial production and practical applications difficult.
[0005] Currently, polyamide membranes prepared by interfacial polymerization have an ultra-thin separation layer and a highly cross-linked structure, showing excellent separation performance in water treatment. However, the inherent hydrophilicity of polyamide membranes leads to low permeability in the separation of oily solvents such as hydrocarbons. Fluorinated hydrophobic modification of monomers has become an important strategy to improve the permeability of OSN and OSRO. However, due to their highly cross-linked structure, traditional polyamide membranes still have low permeability to solvents. Therefore, there is an urgent need for a membrane material with good swelling resistance, excellent permeability and high selectivity for light crude oil. Summary of the Invention
[0006] In order to solve the problems of existing membrane materials used for crude oil separation, such as difficulty in balancing separation efficiency and permeability and poor long-term stability, the present invention provides a solvent-resistant polyimide film, a preparation method thereof, and its application in light crude oil separation. The solvent-resistant polyimide film has high flux and can effectively separate organic molecules of different molecular weights. The film has good physical and chemical stability and has good application prospects in the field of light crude oil separation.
[0007] Specifically, the present invention provides the following technical solutions:
[0008] A first aspect of the present invention provides a method for preparing a solvent-resistant microporous polyimide film, comprising the following steps:
[0009] (1) reacting a diamine monomer with a dianhydride monomer in the presence of a catalyst and a first solvent to obtain a polyimide; the diamine monomer comprises a carboxyl-containing diamine monomer;
[0010] (2) dissolving the polyimide in a second solvent to form a first polyimide solution with a concentration of 10 wt% to 50 wt%, forming the first polyimide solution into a film, performing a phase inversion treatment to obtain an intermediate film, and then treating the intermediate film with an organic solution containing divalent and / or polyvalent metal ions to obtain a supporting base film after a first cross-linking reaction;
[0011] (3) dissolving the polyimide in a third solvent to form a second polyimide solution with a concentration of 0.01 wt% to 5 wt%, coating the second polyimide solution on at least one side of the supporting base film, and forming a polyimide modified layer after drying, and then treating the polyimide modified layer with an organic solution containing divalent and / or polyvalent metal ions, and obtaining the solvent-resistant microporous polyimide film after a second cross-linking reaction.
[0012] The present invention introduces a carboxyl-containing diamine monomer so that the prepared polyimide segment contains carboxyl groups. The intermediate membrane formed by the film-forming phase transformation of the carboxyl-containing polyimide can coordinate with divalent or multivalent metal ions to achieve cross-linking in the carboxyl groups in the different polyimide segments contained in the intermediate membrane, thereby effectively improving the solvent resistance of the formed polyimide membrane; the prepared solvent-resistant polyimide membrane is used as a supporting base membrane, and by controlling the concentration of the carboxyl-containing polyimide organic solution, a carboxyl-containing polyimide organic solution of appropriate concentration is coated on the supporting base membrane, and the modified layer is coordinated and cross-linked with metal ions to form a modified layer of appropriate thickness and density. The microporous polyimide film prepared by the above method not only has excellent solvent resistance and physicochemical stability, but also has good separation ability for low molecular weight hydrocarbon solvents, and can be used for the separation of light crude oil.
[0013] Furthermore, in step (1), the carboxyl diamine monomer is selected from at least one monomer having the structural formula NH2-R"-NH2, wherein R" is selected from one of the following structural formulas:
[0014]
[0015] In the above structural formula, the “——” connected to the benzene ring is a covalent bond connecting the benzene ring and the amino group.
[0016] Furthermore, in step (1), the diamine monomer further comprises at least one diamine monomer that does not contain a carboxyl group, and the diamine monomer that does not contain a carboxyl group is selected from at least one monomer having the structural formula NH2-R'-NH2, wherein R' is selected from one of the following structural formulas:
[0017]
[0018] In the above structural formula, the “——” connected to the benzene ring is a covalent bond connecting the benzene ring and the amino group.
[0019] Furthermore, in step (1), the dianhydride monomer is selected from at least one of the structural formula A monomer, wherein R is selected from one of the following structural formulas:
[0020]
[0021] In the above structural formula, the “——” connected to the benzene ring is a covalent bond connecting the benzene ring and the carbonyl group.
[0022] In some preferred embodiments, R in the dianhydride monomer structure is selected from one of the following structural formulas:
[0023]
[0024] More preferably, the diamine monomer and / or the dianhydride monomer contains fluorine atoms to increase the lipophilicity of the prepared supporting base film and the modified layer, which is beneficial to improving the permeability of oily solvents.
[0025] Furthermore, in step (1), the molar ratio of the diamine monomer to the dianhydride monomer is 1:1; preferably, the molar ratio of the carboxyl-containing diamine monomer in the diamine monomer is 1%-99%, such as 5%, 10%, 15%, 20%, 25%, 30%, 40%, 50%, 60%, 70%, 80%, 90%, etc., including but not limited to the molar ratios listed above. The present invention simultaneously introduces a carboxyl-containing diamine monomer and a carboxyl-free diamine monomer, and regulates the density of the intermediate film and the metal ion coordination crosslinking points by regulating the ratio of the two additions, so that the coordinated crosslinked polyimide membrane has both excellent solvent resistance and high membrane flux.
[0026] Furthermore, in step (1), the first solvent comprises m-cresol and / or N-methylpyrrolidone, and preferably, the boiling point of the first solvent is greater than the reaction temperature.
[0027] Furthermore, the reaction temperature is preferably 160-230° C., and the reaction time is preferably 5-10 h.
[0028] In some preferred embodiments, the diamine monomer is first dissolved in the first solvent, and then the dianhydride monomer is added in batches to form a reaction system with a total solid content of 100-500 g / L.
[0029] Furthermore, in step (1), during the reaction, water generated by the reaction is removed by azeotropic dehydration with toluene, thereby promoting the reaction.
[0030] Furthermore, in step (2), the second solvent includes one or more of m-cresol, N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone and tetrahydrofuran to dissolve the polyimide.
[0031] Furthermore, in step (2), the first polyimide solution is formed into a film using a method for preparing a flat film, specifically as follows: the polyimide is fully dissolved in a second solvent, stirred, and then allowed to stand or vacuumed to remove bubbles; a scraper is used to coat the first polyimide solution after the above treatment on a non-woven fabric fixed on a glass plate to form a uniform and bubble-free film, and the thickness of the film on the substrate surface is 100-300 μm; the glass plate with the film is then transferred to a coagulation bath for phase inversion, and an intermediate film is obtained after the phase inversion is complete; preferably, the coating is carried out at a temperature of 20-30°C and a humidity of 10%-80%, and the solvent for the phase inversion treatment includes water and / or ethanol.
[0032] Furthermore, in step (2), the divalent metal ions include Cu 2+ 、Zn 2+ 、Ni 2+ 、Co 2+ Mg 2+ , Ca 2+ One or more of the polyvalent metal ions, wherein the polyvalent metal ions include Fe 3+ 、Al 3+ 、La 3+ One or more of .
[0033] Furthermore, in step (2), the organic solution containing divalent and / or polyvalent metal ions is prepared by dissolving the corresponding metal salt in an organic solvent. Preferably, the organic solvent is selected from one or more of methanol, ethanol, isopropanol, and acetone.
[0034] In some preferred embodiments, the organic solution containing divalent and / or polyvalent metal ions is a methanol solution of copper nitrate.
[0035] Furthermore, in step (2), the concentration of the organic solution containing divalent and / or polyvalent metal ions is preferably 0.1-1 mol / L, for example, 0.1 mol / L, 0.2 mol / L, 0.3 mol / L, 0.4 mol / L, 0.5 mol / L, 0.6 mol / L, 0.7 mol / L, 0.8 mol / L, 0.9 mol / L, 1.0 mol / L, etc., including but not limited to the concentration values listed above.
[0036] Furthermore, in step (2), the temperature of the first cross-linking reaction is preferably 30-60° C., and the time is preferably 24-48 h. The carboxyl groups in the different polyimide segments contained in the intermediate film can coordinate with divalent or polyvalent metal ions to achieve cross-linking.
[0037] Furthermore, in step (3), the concentration of the second polyimide solution is preferably 0.1wt%-1wt%, such as 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, 1wt%, etc., including but not limited to the concentration values listed above. The concentration of the second polyimide solution will affect the pore size of the supporting base membrane and the thickness of the prepared modified layer. If the concentration of the second polyimide solution is too low, when the surface of the supporting base membrane is coated, the second polyimide solution will easily penetrate into the interior of the supporting base membrane and block the permeation channel of the base membrane, affecting the permeation flux of the solvent; however, the concentration of the second polyimide solution should not be too high. To ensure the integrity of the modified layer, using a second polyimide solution with too high a concentration to prepare the modified layer will result in the thickness of the modified layer being too thick, thereby affecting the permeation flux of the solvent. Therefore, in order to improve the separation efficiency while ensuring the separation effect, it is necessary to use a second polymer solution with an appropriate concentration to prepare the modified layer, preferably 0.1 wt%-1 wt%, more preferably 0.5 wt%.
[0038] Furthermore, in step (3), the coating method includes spin coating, specifically: dissolving the polyimide in a third solvent, removing insoluble impurities with a PTFE filter head with a pore size of 0.45 μm, and obtaining a uniform second polyimide organic solution; attaching the supporting base film flatly to the silicon wafer, and after air-drying in the air, placing the silicon wafer on the vacuum chuck of the coating machine, and quickly dripping the second polymer organic solution onto the supporting base film, and rotating it in a N2 atmosphere according to a specific program; preferably, the spin coating speed is 2000-6000 rpm.
[0039] Furthermore, in step (3), the divalent metal ions include Cu 2+ 、Zn 2+ 、Ni 2+ 、Co 2+ Mg 2+ , Ca2+ One or more of the polyvalent metal ions, wherein the polyvalent metal ions include Fe 3+ 、Al 3+ 、La 3+ One or more of .
[0040] Furthermore, in step (3), the concentration of the organic solution containing divalent and / or polyvalent metal ions is preferably 0.1-1 mol / L, for example, 0.1 mol / L, 0.2 mol / L, 0.3 mol / L, 0.4 mol / L, 0.5 mol / L, 0.6 mol / L, 0.7 mol / L, 0.8 mol / L, 0.9 mol / L, 1.0 mol / L, etc., including but not limited to the concentration values listed above.
[0041] Furthermore, in step (3), the temperature of the second cross-linking reaction is preferably 30-60° C., and the time is preferably 24-48 hours.
[0042] The second aspect of the present invention provides a solvent-resistant microporous polyimide film prepared by the preparation method of the first aspect, wherein the solvent-resistant microporous polyimide film comprises a supporting base film and a metal ion cross-linked carboxylated polyimide modified layer modified on at least one side of the supporting base film;
[0043] The supporting base film and the metal ion cross-linked carboxylated polyimide modified layer both contain a plurality of polyimide polymer chain segments coordinated and cross-linked with metal ions.
[0044] Furthermore, the polyimide polymer chain segment includes a first repeating unit and a second repeating unit, and the ratio of the polymerization degree of the first repeating unit to the second repeating unit is (1-99): (1-99); the first repeating unit includes a condensation unit formed by a diamine monomer containing a carboxyl group and a dianhydride monomer, and the second repeating unit includes a condensation unit formed by a diamine monomer not containing a carboxyl group and a dianhydride monomer.
[0045] Furthermore, the polyimide polymer chain segment includes the following general structural formula:
[0046]
[0047] Wherein, m is any integer from 10 to 1000, n is any integer from 10 to 1000, and m:n=(1-99):(1-99).
[0048] In some preferred embodiments, the intermediate film and / or the polyimide modified layer is treated with an organic solution containing copper ions, so that the intermediate film and / or the polyimide modified layer contain a plurality of polyimide polymer segments coordinated with the copper ions, with R "as For example, a supporting base film or a metal ion cross-linked carboxylated polyimide modified layer having the following cross-linked structure is formed:
[0049]
[0050] Furthermore, the thickness of the supporting base film is 200-300 μm, and the thickness of the metal ion cross-linked carboxylated polyimide modified layer is 100-120 nm. Such an ultra-thin coating thickness can provide excellent permeability for organic solvents.
[0051] Furthermore, the water contact angle of the solvent-resistant microporous polyimide film is 80°-100°.
[0052] Furthermore, the molecular weight cut-off at which the solvent-resistant microporous polyimide film has a rejection rate of not less than 80% is 170 Da.
[0053] The third aspect of the present invention provides an application of the solvent-resistant microporous polyimide film described in the second aspect in toluene / triisopropylbenzene separation or light crude oil separation.
[0054] Furthermore, the solvent-resistant microporous polyimide film has a membrane flux of 0.05-1 Lm -2 h -1 bar -1 The rejection rate of triisopropylbenzene is 80%-99%. The membrane flux of the solvent-resistant microporous polyimide film can be further increased by pressurizing or heating, and the rejection rate will be slightly reduced.
[0055] Compared with the prior art, the present invention has the following beneficial effects:
[0056] 1. The present invention provides a solvent-resistant microporous polyimide film, which utilizes the coordination cross-linking between metal ions and carboxylated polyimide to form a supporting base membrane with excellent solvent resistance and high flux, and by arranging a metal ion-crosslinked carboxylated polyimide modification layer with appropriate thickness and density on the above-mentioned supporting base membrane, a microporous polyimide film with a multi-level pore structure is formed. The film not only has excellent solvent resistance, but also maintains a high membrane flux for hydrocarbon solvents, and exhibits good separation performance in toluene / triisopropylbenzene separation and light crude oil separation.
[0057] 2. The preparation process of the solvent-resistant microporous polyimide film provided by the present invention is simple and easy to operate, with strong controllability and good repeatability, and is suitable for large-scale production; and the prepared solvent-resistant microporous polyimide film has both high membrane flux and good separation performance for hydrocarbon solvents, and maintains stable membrane flux and retention rate of the target object during the continuous 144-hour test time, showing good long-term stability, and has good application prospects in toluene / triisopropylbenzene separation or light crude oil separation. BRIEF DESCRIPTION OF THE DRAWINGS
[0058] Figure 1 Schematic diagram of the synthetic route for preparing the polyimide copolymer containing carboxyl groups according to Examples 1-6 of the present invention;
[0059] Figure 2 The NMR images of the polyimide copolymers containing carboxyl groups prepared in Examples 1, 5, and 6 of the present invention;
[0060] Figure 3 Graphs showing contact angles of the solvent-resistant microporous polyimide films prepared in Examples 1, 5, and 6 of the present invention with water, diiodomethane, and toluene;
[0061] Figure 4 Graphs showing toluene flux and triisopropylbenzene rejection performance of the solvent-resistant microporous polyimide films prepared in Examples 1, 5, and 6 of the present invention before and after the second crosslinking;
[0062] Figure 5 FT-ICR MS spectra of the raw material (undiluted crude oil) and permeate collected from the crude oil separation experiment of the solvent-resistant microporous polyimide film prepared in Example 5 of the present invention. DETAILED DESCRIPTION
[0063] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which the present invention pertains. The terms used herein in the specification of the present invention are for the purpose of describing specific embodiments only and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more of the relevant listed items. The term "includes" or "comprising" described in the present invention means that in addition to the components described, it may also include or contain other components. The term "includes" or "comprising" described in the present invention may also be replaced by the closed form "for" or "consisting of..."
[0064] The present invention will be further described below with reference to specific embodiments and accompanying drawings so that those skilled in the art can better understand and implement the present invention. However, the embodiments are not intended to limit the present invention.
[0065] The Chinese meanings of the English codes of the materials involved in the present invention are: DABA is 3,5-diaminobenzoic acid; 6FDA is 4,4'-(hexafluoroisopropylene) diphthalic anhydride; tmPDA is 2,3,5,6-tetramethyl-1,4-phenylenediamine; pPDA is 1,4-phenylenediamine; TBDN is 3,9-dinitro-4,10-dimethyl-6H,12H-5,11-methylenedibenzo[b,f][1,5]diazocine TBDA is 3,9-diamino-4,10-dimethyl-6H,12H-5,11-methylenedibenzo[b,f][1,5]diazocine; NMP is ultra-dry N-methylpyrrolidone; THF is tetrahydrofuran; Toluene is toluene; DMF is N,N'-dimethylformamide; Acetone is acetone; Methanol is methanol; TIPB is triisopropylbenzene; Pristane is pristane; nC 22 H 46 is n-docosane; p-xylene is p-xylene; o-xylene is o-xylene; isooctane is isooctane; mesitylene is mesitylene; 1-methylnaphthalene is methylnaphthalene.
[0066] Example 1
[0067] This embodiment relates to the preparation of a solvent-resistant microporous polyimide film Cu-c-tmPDA, as follows:
[0068] (1) Preparation of polyimide copolymer c-tmPDA containing carboxyl groups:
[0069] After dissolving DABA (0.02 mol) and diamine monomer tmPDA (0.03 mol) in 120 mL of ultra-dry NMP under N2 atmosphere, dianhydride monomer 6FDA (0.05 mol) solid was added. Then, the mixture was stirred in a three-necked flask for 24 hours, and the amino group and the anhydride group were substituted by nucleophilic substitution to form polyamide acid at room temperature. Subsequently, a water separator and a reflux condenser were placed on the three-necked flask, and 20 mL of anhydrous toluene was added to the three-necked flask and the water separator. The reaction temperature was gradually increased to 200 ° C, and the solution gradually became viscous after the reaction was continued for 5-10 hours. At the same time, water generated by the reaction was continuously produced and received in the water separator. Afterwards, the viscous reaction solution was poured into 2000 mL of anhydrous methanol for precipitation.
[0070] The collected solid polyimide was washed three times in anhydrous methanol, and the methanol was then displaced with ethanol. Finally, the solid was placed in a 60°C forced air oven to remove most of the ethanol, and then dried in a 150°C vacuum oven for 24 hours. The resulting polyimide copolymer containing carboxyl groups was named c-tmPDA.
[0071] (2) Preparation of supporting base film:
[0072] c-tmPDA was dissolved in DMF at a mass percentage of 20 wt% to obtain a first polymer solution with a c-tmPDA mass fraction of 20 wt%; the first polymer solution was uniformly stirred until completely dissolved, and then allowed to stand overnight for degassing to obtain a uniform casting solution.
[0073] At room temperature and 30-40% humidity, the casting solution was cast onto a flat nonwoven fabric using a height-adjustable casting knife (250 μm). The membrane was immediately immersed in deionized water for phase inversion. After 3 hours, the membrane was transferred to another fresh water bath and immersed for 24 hours to complete phase separation, yielding the intermediate membrane.
[0074] The intermediate membrane is immersed in anhydrous methanol to replace the deionized water inside the membrane; a 0.1 mol / L copper nitrate methanol solution is prepared, and the intermediate membrane is immersed in the Cu(NO3)2 methanol solution in a 40°C water bath for 24 hours. The carboxyl-functionalized c-tmPDA polyimide membrane coordinates and cross-links with the metal ions to obtain a supporting base membrane (thickness of 200-300 μm); the supporting base membrane is washed with methanol to remove residual cross-linking agent, and finally it is stored in fresh methanol for future use.
[0075] (3) Preparation of solvent-resistant microporous polyimide film:
[0076] c-tmPDA was dissolved in THF at a mass percentage of 0.5 wt%. Undissolved impurities were then removed using a 0.45 μm PTFE filter to obtain a uniform second polymer solution. The support film was air-dried for 2 hours and then flatly applied to a silicon wafer. The wafer was then placed on the vacuum chuck of a spin coater. A 0.5 wt% second polymer solution was quickly dripped onto the support film and the film was spun at 5000 rpm for 40 seconds in a N2 atmosphere.
[0077] After the polyimide film has dried, it is immersed in a 40°C solution of Cu(NO3)2 in methanol for 24 hours to allow the polymer on the coating to coordinate and crosslink with copper ions, forming a 100-120nm thick metal ion-crosslinked carboxylated polyimide modified layer. The membrane is then washed with methanol to remove any residual crosslinking agent, resulting in a solvent-resistant microporous polyimide film, Cu-c-tmPDA.
[0078] Example 2
[0079] This embodiment relates to the preparation of a solvent-resistant microporous polyimide film Cu-c-tmPDA. The only difference from Example 1 is that the concentration of the second polymer solution is 0.05wt%. The other operations are the same, and the corresponding solvent-resistant microporous polyimide film Cu-c-tmPDA is prepared.
[0080] Example 3
[0081] This embodiment relates to the preparation of a solvent-resistant microporous polyimide film Cu-c-tmPDA. The only difference from Example 1 is that the concentration of the second polymer solution is 0.1wt%. The other operations are the same to prepare the corresponding solvent-resistant microporous polyimide film Cu-c-tmPDA.
[0082] Example 4
[0083] This embodiment relates to the preparation of a solvent-resistant microporous polyimide film Cu-c-tmPDA. The only difference from Example 1 is that the concentration of the second polymer solution is 1wt%. The other operations are the same, and the corresponding solvent-resistant microporous polyimide film Cu-c-tmPDA is prepared.
[0084] Example 5
[0085] This example involves the preparation of a solvent-resistant microporous polyimide film (Cu-c-pPDA). The only difference from Example 1 is that an equimolar amount of the diamine monomer pPDA is used in place of the diamine monomer tmPDA in Example 1. All other procedures are identical. The resulting solvent-resistant microporous polyimide film (Cu-c-pPDA) has a film thickness of 100-120 nm.
[0086] Example 6
[0087] This example involves the preparation of a solvent-resistant microporous polyimide film (Cu-c-TBDA). The only difference from Example 1 is that an equal molar amount of the diamine monomer TBDA is used in place of the diamine monomer tmPDA in Example 1. All other procedures are identical. The resulting solvent-resistant microporous polyimide film (Cu-c-TBDA) has a film thickness of 100-120 nm.
[0088] Comparative Example 1
[0089] This comparative example involves the preparation of a polyimide film c-tmPDA. The only difference from Example 1 is that step (3) does not include the step of soaking in a methanol solution of Cu(NO3)2. The other operations are the same, and the corresponding polyimide film c-tmPDA is prepared.
[0090] Comparative Example 2
[0091] This comparative example relates to the preparation of a polyimide film c-pPDA. The only difference from Example 2 is that step (3) does not include the step of soaking in a methanol solution of Cu(NO3)2. The remaining operations are the same to prepare the corresponding polyimide film c-pPDA.
[0092] Comparative Example 3
[0093] This comparative example relates to the preparation of a polyimide film c-TBDA. The only difference from Example 2 is that step (3) does not include the step of soaking in a methanol solution of Cu(NO3)2. The remaining operations are the same to prepare the corresponding polyimide film c-TBDA.
[0094] Comparative Example 4
[0095] This comparative example relates to the preparation of a solvent-resistant polyimide film. The only difference from Example 1 is that the supporting base film is different. The supporting base film used in this comparative example is prepared as follows: a base film is scraped from commercial P84 polyimide, and the base film is immersed in a 0.2 g / mL isopropanol solution of hexamethylenediamine at room temperature for cross-linking for 12 hours to obtain the supporting base film used in this comparative example; the remaining operations are the same to prepare the corresponding solvent-resistant polyimide film.
[0096] Performance Testing
[0097] The solvent-resistant microporous polyimide films prepared in the above examples and the polyimide films prepared in the comparative examples were tested for one or more of their hydrophobicity, solvent resistance, stability, and separation performance of toluene / triisopropylbenzene and light crude oil, as follows:
[0098] (1) Effect of the concentration of the second polymer solution on the separation performance of the prepared solvent-resistant microporous polyimide film Cu-c-tmPDA
[0099] Using toluene as the solvent and a 1 mol % triisopropylbenzene (TIPB) toluene solution as the separation target, the permeation flux and separation performance of the solvent-resistant polyimide membranes prepared in Examples 1-4 were tested using a dead-end filter at a high pressure of 30 bar. The results are shown in Table 1:
[0100] Table 1
[0101]
[0102] As shown in Table 1, the solvent-resistant microporous polyimide films Cu-c-tmPDA prepared from different concentrations of the second polymer solution all have good retention effects on TIPB, but there are significant differences in toluene flux. Specifically, as the concentration of the second polymer solution increases, the flux of the toluene solvent increases first and then decreases. The toluene flux reaches its highest at 0.5 wt%, while the toluene flux corresponding to a concentration of 0.05 wt% is only 0.05 L m -2 h -1 bar -1 It is speculated that when the second polymer solution is coated on the surface of the supporting membrane, it easily seeps into the supporting membrane and blocks the membrane's permeation channels, significantly reducing the toluene flux. Furthermore, as the concentration increases, the membrane thickness increases, leading to a decrease in permeation flux. In summary, to effectively separate toluene / TIPB while improving separation efficiency, a suitable concentration of the second polymer solution should be used to prepare the modified layer, preferably 0.1wt%-1wt%, and more preferably 0.5wt%.
[0103] (2) Effect of support film type on the separation performance of solvent-resistant polyimide films
[0104] Using toluene as the solvent and a 1 mol% triisopropylbenzene (TIPB) toluene solution as the separation target, the permeation flux and separation performance of the solvent-resistant polyimide membranes prepared in Example 1 and Comparative Example 4 were tested using a dead-end filter at a high pressure of 30 bar. The results are shown in Table 2:
[0105] Table 2
[0106]
[0107] As can be seen from Table 2, the difference between the solvent-resistant polyimide films prepared in Example 1 and Comparative Example 4 is the type of supporting base film. In Comparative Example 4, a solvent-resistant polyimide film is obtained by preparing a metal ion cross-linked carboxylated polyimide modification layer on the surface of a P84 polyimide membrane cross-linked with ethylenediamine. The permeation flux of the polyimide membrane was tested using toluene as the solvent, and the permeation flux was 0, which means it cannot be used to separate toluene / TIPB.
[0108] (3) Effect of diamine monomer type on the hydrophobicity of polyimide films
[0109] The water contact angles of different polyimide films prepared using different diamine monomers in Examples 1, 5, and 6 were tested using a hydrophobic angle meter. The test results are shown in Table 3 below:
[0110] Table 3
[0111] Test Case polyimide film Water contact angle (°) Example 1 Cu-c-tmPDA 89.0 Example 5 Cu-c-pPDA 82.5 Example 6 Cu-c-TBDA 81.9
[0112] As shown in Table 3, the solvent-resistant microporous polyimide films prepared by the present invention have good hydrophobicity. Figure 3 It can be seen that the contact angles of the solvent-resistant microporous polyimide film with the organic solvents diiodomethane and toluene are much smaller than those with water.
[0113] (4) Test of the absorption rate and amount of toluene by different polyimide films
[0114] Toluene was dripped onto the surface of the polyimide film to be tested, and the time for complete absorption was recorded and measured. In addition, the polyimide films to be tested were immersed in toluene, and the mass change of the film was calculated for seven consecutive days to represent the absorption amount. The test results are shown in Table 4 below:
[0115] Table 4
[0116] Test Case polyimide film Complete absorption time (s) Absorption Example 1 Cu-c-tmPDA 18 9.5% Example 5 Cu-c-pPDA 63 15.4% Example 6 Cu-c-TBDA 30 9.3% Comparative Example 1 c-tmPDA Continuous absorption for 7 consecutive days 43.6% Comparative Example 2 c-pPDA Continuous absorption for 7 consecutive days 31.2% Comparative Example 3 c-TBDA Continuous absorption for 7 consecutive days 39.7%
[0117] As shown in Table 4, the solvent-resistant microporous polyimide films prepared according to the present invention absorb little toluene and quickly reach saturation, demonstrating excellent solvent resistance and structural stability. In contrast, the polyimide films prepared in Comparative Examples 1-3, whose surface-modified support films were not cross-linked with metal ions, continued to absorb toluene for up to seven days, with the absorption rates significantly exceeding those of the solvent-resistant microporous polyimide films prepared in Examples 1, 5, and 6.
[0118] (5) Test of the separation performance of different separation membranes for toluene / triisopropylbenzene
[0119] Using toluene as the solvent and a 1 mol% triisopropylbenzene (TIPB) toluene solution as the separation target, the permeation flux and separation performance of the polyimide membrane were tested using a dead-end filter at a high pressure of 30 bar. The results were compared with the existing technology. The results are shown in Table 5:
[0120] Table 5
[0121]
[0122]
[0123] Literature 1: KAThompson, R.Mathias, D.Kim, J.Kim, N.Rangnekar, JRJohnson, SJHoy, I.Bechis, A.Tarzia, KEJelfs, BAMcCool, AGLivingston, RPLively, MMGFinn, N-Aryl-linked spirocyclic polymers for membrane separations of complex hydrocarbon mixtures.Science 369,310-315(2020);
[0124] Document 2: HYJang, JRJohnson, Y.Ma, R.Mathias, DABhandari, RPLively, Torlon(R)hollow fiber membranes for organic solvent reverse osmosisseparation of complex aromatic hydrocarbonmixtures.AIChE J.65,e16757(2019).
[0125] As shown in Table 5, the series of separation membranes disclosed in the literature are used to separate toluene / TIPB. The separation membranes with higher toluene flux have lower rejection rates for TIPB, which are all less than 60%. The separation membranes with a rejection rate of TIPB can reach 91%. Its flux to toluene is only 0.01 L m -2 h -1 bar -1 , resulting in extremely low separation efficiency. However, the solvent-resistant microporous polyimide membranes prepared in Examples 1, 5, and 6 of the present invention achieved both high toluene flux and high TIPB rejection. Furthermore, after 144 hours of continuous testing, the TIPB rejection of the solvent-resistant microporous polyimide membranes did not significantly decrease, demonstrating excellent and stable separation performance.
[0126] (6) Test of toluene / triisopropylbenzene separation performance of different polyimide films at different temperatures
[0127] The separation performance of the toluene / TIPB mixed solvent was tested at 25°C and 75°C, respectively. The test results are shown in Table 6 below:
[0128] Table 6
[0129]
[0130]
[0131] As shown in Table 6, the toluene permeation flux of the solvent-resistant microporous polyimide film prepared in the present invention increases significantly with increasing temperature, and the TIPB retention rate decreases slightly. This improvement in solvent permeability at high temperature is beneficial to the separation efficiency in actual industrial processes.
[0132] (7) Testing the separation performance of different polyimide films on multi-component mixed solvents
[0133] The solvent-resistant microporous polyimide films prepared in Examples 1, 5, and 6 were used to treat xylene, trimethylbenzene, isooctane, methylnaphthalene, TIPB, pristane, and nC 22 H 46 For separation, the solvents were mixed with toluene at a ratio of 1 mol% to prepare mixed solvents. The retention rates of different solvents are shown in Table 7 below:
[0134] Table 7
[0135]
[0136] It can be seen from Table 7 that the solvent-resistant microporous polyimide film prepared in the present invention has a good screening effect on hydrocarbon solvents with relatively high molecular weight.
[0137] (8) Test of crude oil separation performance
[0138] Using the light crude oil provided by Sinopec as the raw material, the solvent-resistant microporous polyimide membrane prepared in Example 5 was used to separate the raw material under a pressure of 4.0 MPa, and the raw material and permeate components were analyzed by FT-ICR MS. The results are as follows: Figure 5 FT-ICR mass spectrometry analysis showed that the average mass / charge (m / z) ratio of the molecular weight distribution of the permeate was significantly reduced compared to the feed. These results confirm the potential of copper-crosslinked membranes for light crude oil fractionation.
[0139] The above-described embodiments are merely preferred examples for the purpose of fully illustrating the present invention, and the scope of protection of the present invention is not limited thereto. Equivalent substitutions or modifications made by those skilled in the art based on the present invention are within the scope of protection of the present invention. The scope of protection of the present invention shall be subject to the claims.
Claims
1. A method for preparing a solvent-resistant microporous polyimide film, characterized in that: The following steps are involved: (1) reacting a diamine monomer with a dianhydride monomer in the presence of a catalyst and a first solvent to obtain a polyimide; the diamine monomer comprises a carboxyl-containing diamine monomer; (2) dissolving the polyimide in a second solvent to form a first polyimide solution with a concentration of 10 wt% to 50 wt%, performing a phase inversion treatment after the first polyimide solution is formed into a film to obtain an intermediate film, and then treating the intermediate film with an organic solution containing divalent and / or multivalent metal ions to obtain a supporting base film after a first cross-linking reaction; (3) dissolving the polyimide in a third solvent to form a second polyimide solution with a concentration of 0.01wt%-5wt%, coating the second polyimide solution on at least one side of the supporting base film, and forming a polyimide modification layer after drying, and then treating the polyimide modification layer with an organic solution containing divalent and / or polyvalent metal ions, and obtaining the solvent-resistant microporous polyimide film after a second cross-linking reaction.
2. The preparation method according to claim 1, characterized in that: In step (1): The carboxyl-containing diamine monomer is selected from at least one monomer having a structural formula of NH2-R"-NH2, wherein R" is selected from one of the following structural formulas: The diamine monomer further comprises at least one diamine monomer not containing a carboxyl group, and the diamine monomer not containing a carboxyl group is selected from at least one monomer having a structural formula of NH2-R'-NH2, wherein R' is selected from one of the following structural formulas: The dianhydride monomer is selected from at least one structural formula: A monomer, wherein R is selected from one of the following structural formulas:
3. The preparation method according to claim 1 or 2, characterized in that: In step (1), the molar proportion of the diamine monomer containing a carboxyl group in the diamine monomer is 1% to 99%; The reaction temperature is 160-230°C.
4. The preparation method according to claim 1, characterized in that: In step (2), at least one of the following features is included: (1) forming a film from the first polyimide solution using a method for preparing a flat film; (2) The solvent of the phase inversion treatment includes water and / or ethanol; (3) The divalent metal ions include Cu 2+ 、Zn 2+ 、Ni 2+ 、Co 2+ Mg 2+ , Ca 2+ One or more of the polyvalent metal ions include Fe 3+ 、Al 3+ ,La 3+ One or more of; (4) The concentration of the organic solution containing divalent and / or polyvalent metal ions is 0.1-1 mol / L; (5) The temperature of the first cross-linking reaction is 30-60°C and the time is 24-48 hours.
5. The preparation method according to claim 1, characterized in that: In step (3), the concentration of the second polyimide solution is 0.1wt%-1wt%.
6. The preparation method according to claim 1, characterized in that: In step (3), the coating method includes spin coating; the rotation speed of the spin coating is 2000-6000rpm.
7. The preparation method according to claim 1, characterized in that: In step (3), the divalent metal ions include Cu 2 + 、Zn 2+ 、Ni 2+ 、Co 2+ Mg 2+ , Ca 2+ One or more of the polyvalent metal ions include Fe 3+ 、Al 3+ ,La 3+ One or more of; The concentration of the organic solution containing divalent and / or multivalent metal ions is 0.1-1 mol / L; The temperature of the second cross-linking reaction is 30-60° C. and the time is 24-48 hours.
8. A solvent-resistant microporous polyimide film, characterized in that: Prepared by the preparation method according to any one of claims 1 to 7; the solvent-resistant microporous polyimide film comprises a supporting base film and a metal ion cross-linked carboxylated polyimide modified layer modified on at least one side of the supporting base film; The supporting base film and the metal ion cross-linked carboxylated polyimide modified layer both contain a number of polyimide polymer chain segments coordinated and cross-linked with metal ions.
9. The solvent-resistant microporous polyimide film according to claim 8, characterized in that: The thickness of the supporting base film is 200-300 μm, and the thickness of the metal ion cross-linked carboxylated polyimide modified layer is 100-120 nm.
10. Use of the solvent-resistant microporous polyimide film according to claim 8 or 9 in toluene / triisopropylbenzene separation or light crude oil separation.
Citation Information
Patent Citations
Spirocentric Compounds and Polymers Thereof
US20190276454A1
Novel membranes and preparation thereof
US20230140883A1
Thermally crosslinked polytriazole separation membranes
WO2022123497A1
Solvent-resistant polymer nanofiltration membrane as well as preparation method and application thereof
CN111514768A
Multi-layer composite film based on polyimide modification and preparation process thereof
CN112266496A
Cited By
High-temperature-resistant adhesive and preparation method thereof
CN121086751A